1997
DOI: 10.1139/v97-007
|View full text |Cite
|
Sign up to set email alerts
|

The complexation of glucose and other monosaccharides with cyclodextrins

Abstract: Equilibrium constants of complexes between β-cyclodextrin and glucose, galactose, or mannose have been determined by fluorometric competition titrations in water to be as low as K = 1 – 0.5 M−1, in sharp contrast to recently published values for glucose around K = 400 M–1. The pentoses ribose, xylose, and arabinose show association constants between 6.3 and 1.5 M−1, in agreement with published values. Preliminary computer-aided molecular modelling studies suggest that the small values observed for the hexoses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…Using the value of k s , we obtained the log K value for β-CD:glucose complex as 4.24. Hirsch et al [28] have reported the value of 2.62 for log K while the value of −0.22 for log K is reported by Hacket et al [42] from spectroscopic, fluorimetry and calorimetric measurements respectively. Considering the drawbacks of these techniques, we feel that our value of log K for β-CD:glucose complexation is much reliable.…”
Section: Discussionmentioning
confidence: 90%
“…Using the value of k s , we obtained the log K value for β-CD:glucose complex as 4.24. Hirsch et al [28] have reported the value of 2.62 for log K while the value of −0.22 for log K is reported by Hacket et al [42] from spectroscopic, fluorimetry and calorimetric measurements respectively. Considering the drawbacks of these techniques, we feel that our value of log K for β-CD:glucose complexation is much reliable.…”
Section: Discussionmentioning
confidence: 90%
“…The figures suggest that 25b in Fig. 1 b Data from [69] c Data from [70] d Data from [71] Table 3 Association constants (K a ) and thermodynamic parameters, determined by microcalorimetry, for binding of monosaccharides to a-cyclodextrin 22a [76] particular might be a promising component for optically responsive carbohydrate-sensing devices. However, the high binding constants are puzzling, given the size mismatch between 25b (*24 Å diameter) and a monosaccharide (*8 Å ), and this system could probably benefit from further study by complementary techniques.…”
Section: Water Soluble Porphyrinsmentioning
confidence: 99%
“…Unfortunately its spectroscopic properties give little help to studies of carbohydrate recognition, which have therefore employed calorimetry or indirect methods involving displacement of fluorescent dyes. There are inconsistencies in the reported data, [68] but the majority view is that the binding of hexoses is undetectable [65,66] or extremely weak [68] (e.g. K a 0.6 m À1 for d-glucose), [70] while that of pentoses is slightly stronger (e.g.…”
Section: Pentoses Hexoses and Methyl Glycosidesmentioning
confidence: 99%